2014
DOI: 10.1111/iju.12522
|View full text |Cite
|
Sign up to set email alerts
|

Core lower urinary tract symptom score questionnaire: A psychometric analysis

Abstract: Abbreviations & AcronymsObjectives: To analyze the reliability and validity of the Japanese version of the core lower urinary symptom score questionnaire with psychometric methods. Method: The present study included 140 women and 125 men who filled in a core lower urinary symptom score questionnaire while attending two lectures on lower urinary tract symptoms. Missing response rates to individual questions were 1.5-5.3%. After the descriptive analyses including box plot, Cronbach's α coefficients and Spearman'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…The existence of construct validity could be confirmed with factor analytical techniques. The results of the present study indicated that the CLSS questionnaire showed good reliability and validity . In addition, the authors carried out psychometric analyses by sex, and found some difference in correlation of items between men and women.…”
supporting
confidence: 53%
“…The existence of construct validity could be confirmed with factor analytical techniques. The results of the present study indicated that the CLSS questionnaire showed good reliability and validity . In addition, the authors carried out psychometric analyses by sex, and found some difference in correlation of items between men and women.…”
supporting
confidence: 53%
“…In this regard, the core lower urinary tract symptom score is a 10-item tool that has been studied in men and women to assess overall LUTS (including bladder and urethral pain) with good reliability and validity. [50][51][52] Furthermore, the ability to predict who is likely to develop incontinence symptoms in the future could aid the targeting of medical advice and therapy more appropriately. The MESA questionnaire has shown validity on achieving this aim but requires further study in different patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most patients have mixed LUTS and therefore a questionnaire that can identify a range of LUTS may be more useful as a screening tool than a condition‐specific tool. In this regard, the core lower urinary tract symptom score is a 10‐item tool that has been studied in men and women to assess overall LUTS (including bladder and urethral pain) with good reliability and validity . Furthermore, the ability to predict who is likely to develop incontinence symptoms in the future could aid the targeting of medical advice and therapy more appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Other response option types contained in the instruments evaluated included the vertical 101-point scale (specific to the three-level [6] and the five-level [7] EuroQol Five-Dimensional Questionnaire); a single-selection list (identical to the VRS except that categories do not exhibit a logical ordering or size); and a multiple-selection list ranging from 4 to 11 options, with most not limiting the number of options that could be selected (exceptions included the Core Lower Urinary Tract Symptom Diary [22], which asked respondents to select a maximum of three items, for example). Yes/no (17 instruments), number entry fields (8 instruments), free-text fields (3 instruments), and time and date fields (8 and 6 instruments, respectively) were also included in some instruments.…”
Section: Description Of Instrument Response Scale Typesmentioning
confidence: 99%